The effect of zinc supplementation on collagen of periodontitisrat - Praptiwi, Siti Fatimah Muis Soeharyo Hadisaputro, Suryono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Zinc,cofactors of DNA-and RNA-polymerase, having great role in tissue heal-ing. In periodontitis, collagen type 1 the main fiberconstituting periodontal structure is des-troyed and be the main cause of lost of teeth among adult in Indonesia. Zndeficiency is still a nutritional problem. The aim of the study is to obtain the influence of 500 pg Zn supplementation (Zn,1and 200 pg (Zn2)per day for 7 days to periodontal collagen of Periodontitis (PI rat through histologic feature. Method: inthe experimental study with factorial design, 29 adult male Wistar rat were used. Subjects were grouped simple randomly into 6 i.e Healthy (H)at the start, Hatthe end, p, P+Te-tracycline IT), ,P + T+ Zn